PENYELESAIAN WANPRESTASI PERJANJIAN ANTARA PEMILIK BISNIS DENGAN SELEBGRAM DALAM MEMPROMOSIKAN SUATU PRODUK SECARA ONLINE - Umul Khair; Ana Ramadhona (Ensiklopedia of Journal, 2023)
The development of the internet in Indonesia has changed very quickly over time. The large number of online shop accounts that have emerged then makes business and business competition even higher. One way that is widely used by online shop business owners today to get consumers' attention is to use the services of an artist on Instagram, or what is commonly called a "celebgram". The problems studied are the implementation of agreements between business owners and celebrities in promoting a product online and settlement of defaults in the implementation of agreements between business owners and celebrities in promoting a product online. This study uses an empirical juridical approach with primary data and secondary data, then analyzed qualitatively. The results of the study concluded that: The implementation of the agreement between the business owner and the celebrity in promoting a product online has carried out the agreement in good faith, where the implementation of the agreement between the business owner and the celebrity in promoting a product online, in this case the business owner will offer cooperation to the public figure to be able to help market the product. These public figures were then asked to provide endorsement appointments, and the problem in implementing the agreement between the business owner and the celebrity in promoting a product online was the occurrence of a default, namely: carrying out the endorsement, but it was late, and carrying out something, but not according to the agreement.Keywords: default, agreement, business owner, celebgram, online.